Telemedicine in neurology - Kujawska, Agnieszka; Perkowski, Radosław; Androsiuk-Perkowska, Joanna; Kożuchowski, Marcin; Bieniek, Daria; Domeracki, Mateusz (Journal of Education, Health and Sport, 2019)
IntroductionTelemedicine in neurology has been developed for the last two decades. However, this concept has only been introduced to the emergency scene recently. In the above review current state and prognosis of development of telemedicine would be described.Material and methodsArticles in the EBSCO database have been analyzed using keywords: telemedicine, neurology. The available literature is subjectively selected. Then, the newest version of every paper was searched for.ResultsResults of researches with applications of telemedicine in neurology in emergency, chronic conditions. Moreover, potential costs and benefits were described. ConclusionsThe involvement of stroke specialists also facilitated the diagnosis of other neurological emergencies such as intracerebral hemorrhage, subarachnoid hemorrhage, hypoglycemia and seizure. Potential barriers to the use of this technology include the initial costs of equipment and training of personnel. Further development of telemedicine would possibly improve both emergency and long-term care in neurology.